2018
DOI: 10.18769/ijasos.455638
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk of Bankruptcy of the Companies Participating in the International Strategic Alliance

Abstract: The globalization of world economic processes leads to increased competition, increased risks, with the same causes in different countries, which ultimately can lead business to bankruptcy. The purpose of the study is to develop a rapid assessment tools risks bankrupting companies in international strategic alliances. The methodological basis of the research served as the scientific works of foreign and Russian scientists, expert, mathematical-statistical and analytical methods, systematic approach to address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The economic category of business continuity was the subject of the research by such scientists as E. [2,3,4]. The study of their works showed that there is a direct relationship between business continuity and financial insolvency, leading the business to bankruptcy.…”
Section: The Relevance and Scientific Development Of The Research Topicmentioning
confidence: 99%
“…The economic category of business continuity was the subject of the research by such scientists as E. [2,3,4]. The study of their works showed that there is a direct relationship between business continuity and financial insolvency, leading the business to bankruptcy.…”
Section: The Relevance and Scientific Development Of The Research Topicmentioning
confidence: 99%
“…The result of the study is a financial calculator for forecasting and assessing the financial risks, which is a mathematical tool for diagnosing the impact of changes in factors on financial risks of the company, tuned to the specifics of its activities. [1,2].…”
Section: Introductionmentioning
confidence: 99%